Interleukin‐10 derived from macrophages and/or neutrophils regulates the inflammatory response to LPS but not the response to CpG DNA - Siewe, Lisa; Bollati–Fogolin, Mariela; Wickenhauser, Claudia; Krieg, Thomas; Müller, Werner; Roers, Axel (European Journal of Immunology, 2006)
Interleukin‐10 (IL‐10) is an important regulator of immune responses secreted by different cell types. We have previously shown that mice with selective inactivation of the IL‐10 gene in T cells suffer from deregulated T cell responses similar to those observed in IL‐10–/– animals. Unlike IL‐10–/– mice, however, T cell‐specific mutants do not mount an enhanced innate immune response to LPS, which must, therefore, be subject to control by IL‐10 from non‐T cells. Herein we show that subcutaneous injection of LPS, which causes moderate local inflammation in WT and T cell‐specific IL‐10 mutant mice, results in augmented inflammatory infiltration and extensive tissue necrosis in mice with deficiency for IL‐10 in macrophages and neutrophils. Correspondingly, we observed an enhanced sensitivity of the macrophage/neutrophil‐specific IL‐10 mutants to systemic LPS exposure when compared with WT animals. In contrast, the inflammatory response of these mutants to CpG oligodeoxynucleotides was not different from that of WT mice. While IL‐10–/– mice developed massive inflammation, necrosis and increased serum cytokine levels after subcutaneous CpG injection, only moderate responses were observed in macrophage/neutrophil‐specific IL‐10 mutant and WT mice. These results show that different innate immune responses can be subject to control by IL‐10 from different cellular sources.